Molecular Serotype-Specific Identification of Non-type b Haemophilus influenzae by Loop-Mediated Isothermal Amplification - Takano, Chika; Seki, Mitsuko; Kim, Dong Wook; Kilgore, Paul E.; Fuwa, Kazumasa; Takahashi, Koji; Inazaki, Toshiaki; Hayakawa, Satoshi (Frontiers in Microbiology, 2017)
Over the past four decades, the incidence of meningitis caused by Haemophilus influenzae in children has decreased due to widespread vaccination against H. influenzae type b (Hib). The incidence of invasive diseases due to H. influenzae types not included in the vaccines, however, has increased. At present, there are a limited number of diagnostics available to detect non-type b H. influenzae. To address this issue, we developed a rapid, simple, and cost-effective method for detecting serotypes of H. influenzae. We designed LAMP primer sets based on published sequences for H. influenzae capsular types a, c, d, e, and f. The assay was evaluated to determine test reactivity, specificity, and sensitivity. To support its use in patients with suspected meningitis, we evaluated the detection limit of the non-Hib serotype specific LAMP assay using bacterial genomic DNA-spiked cerebrospinal fluid (CSF) specimens. The reactivity and specificity of the LAMP assays were confirmed using six serotypes and non-typeable H. influenzae strains, plus eight strains of other Haemophilus species and non-Haemophilus genera. The detection limits of the LAMP assay for capsular types a, c, d, e, and f were 10^2, 10^2, 10^2, 10^3, and 10 copies per reaction, while those of the PCR assay were 10^4, 10^4, 10^3, 10^3, and 10^4 genome copies per reaction, respectively. Using DNA-spiked CSF specimens, the detection limit of the LAMP assay was equivalent to that using purified DNA as the template. However, the detection limit of the PCR was reduced from 10^3 to 10^4 genome copies per reaction for serotype d and from 10^3 to 10^5 genome copies per reaction for serotype e. To the best of our knowledge, this is the first report of a serotype-specific identification assay for H. influenzae using the LAMP method. Our results suggest the potential of LAMP methods for patients with suspected meningitis in resource-limited laboratories or public health surveillance systems.